If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 + 6n = -6(1 + -8n) 36 + 6n = (1 * -6 + -8n * -6) 36 + 6n = (-6 + 48n) Solving 36 + 6n = -6 + 48n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-48n' to each side of the equation. 36 + 6n + -48n = -6 + 48n + -48n Combine like terms: 6n + -48n = -42n 36 + -42n = -6 + 48n + -48n Combine like terms: 48n + -48n = 0 36 + -42n = -6 + 0 36 + -42n = -6 Add '-36' to each side of the equation. 36 + -36 + -42n = -6 + -36 Combine like terms: 36 + -36 = 0 0 + -42n = -6 + -36 -42n = -6 + -36 Combine like terms: -6 + -36 = -42 -42n = -42 Divide each side by '-42'. n = 1 Simplifying n = 1
| x^2+12=24+x | | x-8.8=6.1 | | 2x+6(-2x-4)=-29-5x | | log[4](-4x)=1 | | 11e-12+9e-16=13e+42 | | 7x+5(x-9)= | | -5x+165=-3x+153 | | -6(-6+4x)=3x-18 | | 44428=974x+17156 | | 97=-7(x-7)-5x | | 2x^2-12x-34=0 | | 15x=9x+24 | | -6(4+6x)=-4x-24 | | 24x^2-40x-56=0 | | 52/7-5/14 | | 18-5x-2=-4 | | 7-(m-2)=12 | | 20Q+800=100+Q | | (2x-5)(3x^2-4x+1)=0 | | z^2+10z+11=0 | | 5(x+6)+1=3-2x | | 5(6m+7)=-2-7m | | s-9/10=21/10 | | 2(3w-12+w)=640 | | -9p=-72 | | 1.96x^5-4x^2-16x-16=0 | | 7-7(1-7x)=8x | | p(x)=-2x+100x-25 | | s-7/10=13/10 | | 12y=13.2 | | 5x+1+3=8(3x+2)+7(2-3x) | | 7(2y+1)=3(7+5y) |